(untitled) (Development Service Industry Management, 2024)
The modern digital space produces gigabytes of information every day, the amount of data grows exponentially and needs to be processed, stored and structured. At the same time, the world economy is focused on "smart growth" - development based on accumulated knowledge and innovations, the role of entrepreneurial intuition in management decision-making processes is decreasing, and interest in business analytics is growing. Until recently, companies managed traditional assets - property, money, technology, but the digital age has brought a new type of asset - data from which forecasts, insights and excess profits are generated. The mentioned trends have significantly changed approaches to creating added value, and instead of traditional chains, networks are now forming that use third-party resources instead of their own, prefer communications between users of the digital platform instead of focusing on internal business processes, create values ​​for the entire platform, and not for individual consumers, which provides the platform as an ecosystem with new opportunities, synergy, quantitative and qualitative growth and joint results. And in this context, it is important to investigate the role of business analytics in the organization of work and management of digital platforms, using support systems, making and optimizing decisions based on the aggregation of big data. The article is devoted to the justification of the feasibility of proving the value of business analytics in the management of digital platforms and the formation of an effective system of support and management decision-making on this basis. The authors investigated the distinguishing features of digital platforms according to certain classification features: scope, geographic orientation, technological feature, scope of activity and value creation criteria. Four main methods of business analytics are specified: descriptive, diagnostic, predictive, prescriptive. The value of the systematic use of business analytics in the management of digital platforms is proven and it is emphasized that with its help, reasonable management decisions are made, business processes and technological operations are optimized, strategic development goals are achieved, new products and services are created, user scenarios are simulated, general trends are identified, weak points and possible growth points.